Socioeconomic inequalities in overweight and obesity among 6‐ to 9‐year‐old children in 24 countries from the World Health Organization European region. (28th June 2021) - Buoncristiano, Marta; Williams, Julianne; Simmonds, Philippa; Nurk, Eha; Ahrens, Wolfgang; Nardone, Paola; Rito, Ana Isabel; Rutter, Harry; Bergh, Ingunn Holden; Starc, Gregor; Jonsson, Kenisha Russell; Spinelli, Angela; et al.
Summary: Childhood overweight and obesity have significant short‐ and long‐term negative impacts on children's health and well‐being. These challenges are unequally distributed according to socioeconomic status (SES); however, previous studies have often lacked standardized and objectively measured data across national contexts to assess these differences. This study provides a cross‐sectional picture of the association between SES and childhood overweight and obesity, based on data from 123, 487 children aged 6–9 years in 24 countries in the World Health Organization (WHO) European region. Overall, associations were found between overweight/obesity and the three SES indicators used (parental education, parental employment status, and family‐perceived wealth). Our results showed an inverse relationship between the prevalence of childhood overweight/obesity and parental education in high‐income countries, whereas the opposite relationship was observed in most of the middle‐income countries. The same applied to family‐perceived wealth, although parental employment status appeared to be less associated with overweight and obesity or not associated at all. This paper highlights the need for close attention to context when designing interventions, as the association between SES and childhood overweight and obesity varies by country economic development. Population‐based interventions have an important role to play, but policies that target specific SES groups are also needed to address inequalities.